A simplified high-throughput method for pyrethroid knock-down resistance (kdr) detection in Anopheles gambiae - Walker Edward D; Black William C; Randle Nadine P; McCall P J; Ranson Hilary; Lynd Amy; Donnelly Martin J (Malaria Journal, 2005)
Abstract Background A single base pair mutation in the sodium channel confers knock-down resistance to pyrethroids in many insect species. Its occurrence in Anopheles mosquitoes may have important implications for malaria vector control especially considering the current trend for large scale pyrethroid-treated bednet programmes. Screening Anopheles gambiae populations for the kdr mutation has become one of the mainstays of programmes that monitor the development of insecticide resistance. The screening is commonly performed using a multiplex Polymerase Chain Reaction (PCR) which, since it is reliant on a single nucleotide polymorphism, can be unreliable. Here we present a reliable and potentially high throughput method for screening An. gambiae for the kdr mutation. Methods A Hot Ligation Oligonucleotide Assay (HOLA) was developed to detect both the East and West African kdr alleles in the homozygous and heterozygous states, and was optimized for use in low-tech developing world laboratories. Results from the HOLA were compared to results from the multiplex PCR for field and laboratory mosquito specimens to provide verification of the robustness and sensitivity of the technique. Results and Discussion The HOLA assay, developed for detection of the kdr mutation, gives a bright blue colouration for a positive result whilst negative reactions remain colourless. The results are apparent within a few minutes of adding the final substrate and can be scored by eye. Heterozygotes are scored when a sample gives a positive reaction to the susceptible probe and the kdr probe. The technique uses only basic laboratory equipment and skills and can be carried out by anyone familiar with the Enzyme-linked immunosorbent assay (ELISA) technique. A comparison to the multiplex PCR method showed that the HOLA assay was more reliable, and scoring of the plates was less ambiguous. Conclusion The method is capable of detecting both the East and West African kdr alleles in the homozygous and heterozygous states from fresh or dried material using several DNA extraction methods. It is more reliable than the traditional PCR method and may be more sensitive for the detection of heterozygotes. It is inexpensive, simple and relatively safe making it suitable for use in resource-poor countries.